The World of Ants: A Scenario to Promote the Care of Nature and the Preservation of the Environment With a Group of Kindergartners in a Rural School in Acacías, Colombia - Duque Zuluaga, Ayda Liliana; Galeano González, Ismelda; Cortés Toledo, Alicia; Padilla-Rincón, Mariana (Journal of Childhood Studies, 2026)
This Ideas from Practice article presents an educational experience with kindergarten children in a rural school in Colombia. Sparked by the question “Who bit my cookie?”, an inquiry project with ants emerged that integrated key activities such as play, art, exploration, and literature. Through an action research methodology, the project fostered scientific skills and critical thinking in the children, as well as attitudes of care toward the natural environment. Ants, observed in their everyday lives, became teachers and learning companions. This experience shows how wonder, curiosity, and active listening can open pathways to a situated, ethical, and relational pedagogy in early childhood.